Bone Marrow Stem Cell as a Potential Treatment for Diabetes - Ming Li; Susumu Ikehara (Journal of Diabetes Research)
Diabetes mellitus (DM) is a group of metabolic diseases in which a person has high blood glucose levels resulting from defects in insulin secretion and insulin action. The chronic hyperglycemia damages the eyes, kidneys, nerves, heart, and blood vessels. Curative therapies mainly include diet, insulin, and oral hypoglycemic agents. However, these therapies fail to maintain blood glucose levels in the normal range all the time. Although pancreas or islet-cell transplantation achieves better glucose control, a major obstacle is the shortage of donor organs. Recently, research has focused on stem cells which can be classified into embryonic stem cells (ESCs) and tissue stem cells (TSCs) to generate functional β cells. TSCs include the bone-marrow-, liver-, and pancreas-derived stem cells. In this review, we focus on treatment using bone marrow stem cells for type 1 and 2 DM.